Ising model on the semi-infinite Cayley tree of third order with inhomogeneous interactions - Ganikhodjaev, Nasir; Ibrahim, Huda Husna (American Institute of Physics Inc., 2018)
In this paper we investigate the problem of phase transition for Ising model on a semi-infinite Cayley tree of third order with inhomogeneous left, middle and right parameters describing the strength of the interactions between left, middle and right nearest-neighbors respectively. We produce a recurrent equation that describes a limit behavior of the sequence conditional Gibbs measures and prove that if at least two of the parameters are positive one can reach phase transition.